Klinik Hukum Berbasis Etika Profesi untuk Penguatan Pendidikan Karakter Mahasiswa Hukum dalam Pengabdian kepada Masyarakat - Khairul Umam; Achmad Taufik; Ria Kasanova (Lembaga Pengembangan Kinerja Dosen, 2026)
Legal education in higher education institutions remains predominantly dominated by cognitive approaches, which have not fully succeeded in shaping students’ character, particularly in terms of integrity, professional responsibility, and legal empathy. This condition highlights the need for learning approaches that integrate practical experience with professional ethical values. This community engagement activity aims to strengthen the character of law students through a clinical legal education-based intervention integrated with professional ethics education. The activity was conducted using a participatory approach involving 35 law students from the Faculty of Law at Universitas Madura over the period from 21 April to 13 May 2026. The intervention consisted of a series of activities, including legal education sessions, basic legal consultations, and structured ethical reflection. The community partners were local residents with limited access to legal information and services.The results indicate an improvement in students’ character scores across several dimensions, namely integrity (from 3.42 to 4.21), professional responsibility (from 3.51 to 4.28), and legal empathy (from 3.37 to 4.35). In addition, more than 80% of students reported that the activity enhanced their understanding of legal practice and the social conditions of the community. The activity also had a positive impact on the community, particularly in improving legal literacy. These findings demonstrate that experience-based legal clinics are effective in strengthening law students’ character while simultaneously providing tangible benefits to the community. Therefore, community engagement activities based on clinical legal education can be developed as a strategic medium for strengthening character education in law faculties.